Tingkat Kesadaran Etika Informasi Islam pada Mahasiswa Semester 2 Universitas Muhammadiyah Mataram - Muhammad Soadikin; Cici Nurmianty; Nasrullah Nasrullah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
The development of information technology in the digital age not only provides easy access to information but also raises ethical issues such as hoaxes, disinformation, and a lack of responsibility in the use of digital media. This study aims to analyze the level of awareness of Islamic information ethics among second-semester students at Muhammadiyah University of Mataram. The study employed a descriptive quantitative approach, using a Likert-scale questionnaire to collect data from 90 respondents selected through purposive sampling based on the following criteria: active second-semester students, having taken the course “Al-Islam and Muhammadiyah Studies,” active users of social media, and willing to participate as respondents. The research instrument was tested for validity using Pearson’s Product-Moment correlation, with all items deemed valid (calculated r > 0.207), and for reliability using Cronbach’s Alpha, yielding a value of 0.967, indicating very high reliability. The results of the study indicate that the level of awareness of Islamic information ethics falls into the high category (mean 4.12; 82.4%). This study contributes to strengthening research on digital literacy based on Islamic values as a foundation for shaping ethical and responsible digital behavior among students.